2022
DOI: 10.3390/ijerph19020718
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Ease of Removal of Fractured NiTi Endodontic Rotary Files from the Root Canal System—An In Vitro Study

Abstract: This study aimed at analyzing and comparing the ease of removal of fractured nickel–titanium (NiTi) endodontic rotary files from the root canal system between the ultrasonic tips and the Endo Rescue appliance removal systems, as well as comparing the volume of dentin removed between ultrasonic tips and the Endo Rescue appliance using a micro-computed tomography (micro-CT) scan. Material and Methods: Forty NiTi endodontic rotary files were intentionally fractured in 40 root canal systems of 20 lower first molar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The ProTaper Next X2 rotary file was partially notched to half of the instrument thickness with a diamond disc mounted on a low-speed handpiece, as per Faus-Matoses et al (14) , at 5mm from the tip. The file was introduced into the mesiobuccal canal, and at a speed of 350 rpm and torque of 3.5 N, it was rotated with pressure until separation at a depth of three mm apical to the canal orifice to be visible under the DOM.…”
Section: Instrument Separation Inside the Root Canalmentioning
confidence: 99%
“…The ProTaper Next X2 rotary file was partially notched to half of the instrument thickness with a diamond disc mounted on a low-speed handpiece, as per Faus-Matoses et al (14) , at 5mm from the tip. The file was introduced into the mesiobuccal canal, and at a speed of 350 rpm and torque of 3.5 N, it was rotated with pressure until separation at a depth of three mm apical to the canal orifice to be visible under the DOM.…”
Section: Instrument Separation Inside the Root Canalmentioning
confidence: 99%
“…When instrument fracture occurs, several treatment strategies can be used: trying to remove the instrument, attempting to bypass the instrument, or sealing the root segment occupied by the broken instrument [3]. Studies using ultrasonic instrumentation to remove broken segments have reported favorable results [4], with success rates of 54.4% to 93.3%. Ultrasonic file removal methods are mostly based on the Ruddle technique or a variation of it [5].…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonic file removal methods are mostly based on the Ruddle technique or a variation of it [5]. A platform is created using a Gates-Glidden drill (2)(3)(4) prior to instrument use. The Gates-Glidden drill is modified by cutting through the maximum cross-sectional diameter perpendicular to its longitudinal axis.…”
Section: Introductionmentioning
confidence: 99%